The Effectiveness of the Problem Based Learning Model in Forming Students' Thinking Skills in the Material of Cooperation and Mutual Cooperation - Aldi Arya Pratama; Ratna Kartikawati; Eko Priyanto (Proceedings Series on Social Sciences & Humanities, 2024)
The Effectiveness of the Problem Based Learning Model in Shaping Students' Thinking Skills on Cooperative and Cooperative Materials. This study aims to find out how effective the Problem Based Learning learning model is in shaping critical thinking skills in the Youth Pledge material. The method used in this study is a quasi-experiment with a nonequivalent control group design. The samples used were class VII A as the experimental class (n=32) and VII C as the control class (n=32). The data collection techniques used in this study are instruments in the form of questionnaires, observations and documentation studies that are analyzed with alternative tests paired sample test and independent sample t-test with results of 0.000 < 0.05 which means that the Problem Based Learning learning model is effective in shaping students' critical thinking skills. This is shown from the results of the n-gain present test of the experimental class of 61.81% and the results of the n-gain present test of the control class of 34.31%. The results of the effect size test obtained a value of 2.61 which is included in the high-impact category.